Humanistic nursing curriculum needs: a cross-sectional survey in Shenzhen, China - Jiang, Yurong; Gao, Yuan; Li, Shanshan; Zhong, Haiyan; Xia, Hulu; Lin, Lian; Zhou, Qi; Liu, Yan (Frontiers in Medicine, 2025)
BackgroundThis study aimed to assess the training needs of nursing professionals for developing a structured humanistic nursing curriculum, emphasizing practical and theoretical components.MethodsA cross-sectional survey was conducted from January to June 2024 at Shenzhen People’s Hospital, involving 486 nursing staff members. The survey collected demographic data and training preferences across six modules: Humanistic Management, Literacy, Practice, Innovation, Care, and Education. Preferred training methods and course structures were also evaluated. Descriptive statistics were used to analyze participant responses.ResultsAmong participants, 89.3% were female, with 55.35% aged 25–35 years, and 85.39% holding a bachelor’s degree. The highest demand was observed for Humanistic Management (87.04%) and Humanistic Literacy (86.42%). Courses on listening skills (94.76%) and the connotation of humanistic nursing (89.6%) ranked highest. Most participants (46.3%) preferred a training model with two-thirds practical learning, and online courses (79.01%) and workshops (75.93%) were the most favored methods.ConclusionThe findings highlight the need for a structured humanistic nursing training program with an emphasis on interactive, practice-oriented learning. Future curricula should integrate emotional regulation, communication skills, and humanistic innovation to enhance patient-centered care. Further research is recommended to evaluate the long-term impact of such training on nursing practice and healthcare outcomes. Because data were collected through convenience sampling from a single tertiary hospital, the findings are not generalizable to broader nursing populations.